The Paradox on IT Literacy and Science’s Learning Achievement in Secondary School - Sulisworo, Dwi (Institute of Advanced Engineering and Science, 2013)
Higher education is currently in the rapid change process. These changes are driven by many factors, both internal and external. Some trends in higher education development occur on a wider social context. People feel more comfortable with using the internet as a tool in the day-to-day teaching and learning activities. Information and communication technologies have an important role to help improve teaching and learning process. The aim of this research is to determine whether the student IT literacy medium influence the learning achievement of sciences subject. This research is a quantitative research using multivariate statistical analysis techniques. The result shows that IT literacy has no effect on learning achievement. This phenomenon indicates the paradox on learning and ICT issues.DOI: http://dx.doi.org/10.11591/ijere.v2i4.2732